A magyar földrajztudomány és az Osztrák-Magyar Monarchia, 1867-1918: THE HUNGARIAN GEOGRAPHY AND AUSTRO-HUNGARIAN MONARCHY 1867-1918 - Hajdú, Zoltán (Közép-Európai Közlemények, 2020)
Modern geography was born in the second half of the 19th century and developed fast throughout that period internationally. After the Austro-Hungarian Compromise of 1867 the Hungarian science was set on a new, modernising and evolving path. As the scale and scope of higher education increased, a department of geography was formed at the Budapest University. The institutionalisation of geography (department, scientific society, academic journal) underwent rapidly at the beginning of the 1870s. In the current paper we present the development and characteristics of the Hungarian geography during the Age of Dualism (1867–1918), and in particular its view on the Austro-Hungarian Monarchy.